A body force model to assess the impact of a swimmer`s arm on propelled swimming resistance - Banks, J.; Phillips, A. B.; Hudson, D. A.; Turnock, S. R. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
The dynamic forces acting on a swimmer`s body are notoriously difficult to measure experimentally, thus motivating many researchers to use computational fluid dynamics to assess the propulsion and resistance forces. To assess both the thrust generated and the self-propelled resistance, fully dynamic simulations are required, including the large range of body motions involved in swimming. This comes with a heavy computational cost and often limits the ability of the method to resolve detailed flow features associated with resistance force. This article applies a body force approach to propelled swimming simulations by combining an unsteady Reynolds Averaged Navier-Stokes simulation of the passive resistance with momentum source terms which accelerate the fluid in the location of the arm to represent the impact the arm has on the flow. Both passive and active towed swimming experiments were conducted and compared with the simulations. Despite observing a 24% variation in the pressure resistance associated with the arm entry, the arms had no significant effect on the mean propelled resistance of a swimmer. The passive resistance methodology agreed well with experimental data.